MANAJEMEN KONFLIK ORGANISASI DALAM PERSPEKTIF ISLAM - Yani Tri Wijayanti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
An organizatin made up of people who become members of the organization, they interact with each other. Conflict occurs within an organization when there are two conflicting parties. Conflict can be positive and negative effect, it depends on how the leadership of the organization is able to manage existing conflicts.Effective conflict management can improve organizational effectiveness, one way is to negotiate. Islam also teaches to negotiate in resolving disputes. This article provides resolution of conflicts within the organization in the Islamic perspective with negotiating.